PENYALAH GUNAAN NAZA (Narkotika dan Zat aditif lainnya) OLEH INSAN PENERBANGAN DAN ANCAMAN TERHADAP KESELAMATAN PENERBANGAN - Fatchoelqorib, Mochammad; Setiadi, Bekti (STP AVIASI, 2018)
Since the Government of Indonesia made deregulation in several aspect of aviation industry early of this century, the development of airline industry shows thremendestly. There are many new Low Cost Air Carrier â€œgrowing up like mushrum in the rainy seasonâ€. Some of side effect of this fast growing are concerning with flight safety, especialy in maintenance, human resources and operational aspects. Flight Safety is mandatory in all aspect of aviation industry, there is no room for relaxation or dispensation regarding safety. Air crew especialy Pilot has huges responsibility in Flight Safety during flight, their healthy condition and eligibility of technical of flight should be maintain at all times. Missuse of narcotic will jeoperdize both healthy and ability in their profesional perform.Â In this journal we will focus on human resources aspect regarding legislation of missuse of narcotic among flight crew and implementation of safety management of aviation personel.